Provisional Agenda for the Thirty-Second Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2015)
The following is the provisional agenda for the Thirty-Second Meeting of the International Monetary and Financial Committee, which is to be convened in Lima, Peru, October 9-10, 2015.